Market Price Dissemination and Farmers' Pesponse: A case study from Ogun State of Nigeria - OLUDIMU, OLUFEMI (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Some aspects of news dissemination on market prices and supplies in Ogun State of Nigeria were studied. Primary and secondary data were utilised in identifying the flow of information and the problems faced by farmers with regard to the market intelligence aspect of their farming operations. It was found that farming did not receive as much attention as the other major programmes transmitted on the radio which is the most common medium through which farmers obtained information. It is suggested that higher levels of response to agricultural production call for greater improvements in communicating farm and market news to farmers.